The effect of couples\' supportive counseling on self-care behavior in women with insulin-treated gestational diabetes: A randomized clinical trial - Sahar Rostampour; Fatemeh Erfanian Arghavanian; Masoumeh Kordi; Mohammad Taghi Shakeri; Farideh Akhlaghi; Seyyed Mohsen Asghari Nekah (Tehran University of Medical Sciences, 2020)
Background & Aim: Gestational diabetes mellitus is the most common medical disorder during pregnancy that has many negative psychosomatic effects on the pregnant women and their fetus. According to existing studies, the role of counseling and husband's support in gestational diabetes has been less studied, so the present study aimed to determine the effect of coupleschr('39') supportive counseling on self-care behavior in women with insulin-treated gestational diabetes. Methods & Materials: In this randomized clinical trial, 64 pregnant women (26-30 weeks of gestation) with gestational diabetes referred to the diabetes clinic of Umm al-Banin Hospital in Mashhad in 2018-2019 were divided into the intervention or control groups using the 4-way blocking method. For the women and their husbands in the intervention group, coupleschr('39') supportive counseling was conducted by the researcher in the form of three one-hour sessions with one week interval. A diabetes self-care questionnaire was completed in two stages, before and four weeks after the intervention for both groups, and data were analyzed by independent t-test and paired t test using the SPSS software version 16. Results: There were no statistically significant differences between the two groups in pre-intervention self-care scores (P>0.05). After the intervention, the difference between the mean of self-care scores before and after the intervention in the intervention group was 12.09±7.56 and in the control group was 0.00±3.60, which a significant increase was observed in the self-care score for the intervention group compared to the control group (P<0.001). Conclusion: Coupleschr('39') supportive counseling helps to promote self-care behavior in patients with gestational diabetes and can be used as an effective method to reduce the adverse consequences of gestational diabetes. Clinical trial registry: IRCT20181002041202N1